Contribution of Law and Religious Principles to Eliminating Corruption Culture - Asep Syarifuddin Hidayat; Nur Rohim Yunus; Muhammad Ishar Helmi (Mimbar Agama Budaya, 2022)
Damage will hit the people of a country when corruption has become a culture. However, religion as a way of life for the people is able to contribute to dampening this culture of corruption, so that it can save people from the destruction of their culture of life. The method used in this study is a qualitative method with a literate approach. The results of the study stated that religion greatly contributed to reducing the culture of corruption. However, there are still challenges for religion to be able to contribute to reducing the culture of corruption, including the limited involvement of religious leaders in political issues, religious differences, lack of coordination between religious institutions and the government, cultural and social environmental factors, lack of supervision and strict law enforcement. In addition, there are limitations of religious leaders in their mastery of general science and technology.Keywords: Corruption Culture; Religion; Contribution